BIOAVAILABILITY ENHANCEMENT BY FLOATING MICROBALLOONS OF DIPYRIDAMOLE AND CLOPIDOGREL: IN VIVO PHARMACOKINETIC STUDY - KRISHNA, SEELAM RAMYA; RAMU, A.; VIDYADHARA, S.; RANI, A. PRAMEELA (International Journal of Applied Pharmaceutics, 2021)
Objective: In vivo pharmacokinetic studies of clopidogrel and dipyridamole floating microballoons to check their bioavailability enhancement. Methods: The bioanalytical method development was carried by using HPLC with column Poroshell 120 EC-C 18; 4.6x100 mm. The in vivo pharmacokinetic studies were performed in Wistar male rats and the obtained data from the pharmacokinetic parameters were analyzed using PK Solver software. Results: The developed bioanalytical method was found to be linear in the concentration range of 1-100 ng/ml for clopidogrel bisulfate and 0.02-4µg/ml for dipyridamole with correlation coefficient of 0.9993 and 0.9987 respectively. The study results showed that the method was simple, linear, accurate and precise. The in vivo studies indicated that the AUC was found to be increased by 33.3% and 154.5% for clopidogrel and dipyridamole micro balloons, respectively, when compared to their pure drugs. Conclusion: The bioanalytical methods development and their validation parameters indicated that the methods are accurate, precise and linear in the studied range of concentrations. In vivo test results infer to the effective, sustained release of both the drugs when formulated as micro balloons and increase in the absorption, thereby enhancing the bioavailability of the drugs. The pharmacokinetic studies also confirmed the increase in the mean residence time of the drugs when formulated as floating microballoons.